Effect of foliar feeding of seaweed extract Gofar SeaWeed and compounds of zinc and iron on growth and production of green bean (Phaseolus vulgaris L.). - شحادة, مريم; نصر شيخ سليمان , (Latakia University Journal -Biological Sciences Series, 2023)
- The research was carried out in the village of Al-Sharasher, 3 km north of the city of Jableh In the month of March for the agricultural season 2020-2021 -The aim of the research is to improve the vegetative and fruiting growth of beans from green pods using foliar spray with seaweed extract and zinc and iron sulfate. - Study included Six treatments of foliar spray in addition to the treatment of the control whose plants were sprayed with water only, and the research was followed in the implementation of the randomized complete block design with four replicates for each treatment and 15 plants in each replicate. - The study showed that the plants sprayed with seaweed extract and sulfate of zinc and iron were significantly superior to the plants that were not sprayed, in all indicators of vegetative and flowering growth and the quantity of production. - The results also showed that the plants sprayed with seaweed extract and zinc sulfate were significantly superior to the rest of the treatments, as they recorded the highest values ​​in plant length (296 cm / plant), number of leaves (32 leaves / plant), leaf area (10614) cm (2), and number of flowers (178). flower (and the number of pods is 84.3) and the total production of green pods is 4.11 (kg / m2)l